2014
DOI: 10.1080/00397911.2014.914221
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Highly Efficient Aerobic Oxidative Synthesis of Benzimidazoles, Benzoxazoles, and Benzothiazoles Directly from Aromatic Primary Amines Under Solvent-Free Conditions in the Open Air

Abstract: Experimental sectionGeneral Methods.All starting materials were purchased from commercial sources and used without further treatment.Melting points were determined on a Thomas Hoover capillary apparatus and were uncorrected.All known compounds are identified by appropriate technique such as 1 H NMR and compared with previously reported data. 1 H NMR (500 MHz) was recorded on a Bruker 500 spectrometer with tetramethylsilane (TMS) as an internal standard. Mass spectra were recorded on an Agilent technologies 611… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Many synthetic methods describe the oxidative formation of 2-substituted benzothiazoles from 2-aminothiophenol (Scheme 2, compound 1 ) and aldehydes under various aerobic and dehydrogenative conditions [38, 4345]. Generally, this transformation can be envisioned from the initial, reversible condensation of an aldehyde, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Many synthetic methods describe the oxidative formation of 2-substituted benzothiazoles from 2-aminothiophenol (Scheme 2, compound 1 ) and aldehydes under various aerobic and dehydrogenative conditions [38, 4345]. Generally, this transformation can be envisioned from the initial, reversible condensation of an aldehyde, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…performed the aerial oxidation of aromatic primary amines ( 81 ) and 4 , by using 5 mol % of Fe (NO 3 ) 3 and TEMPO (2,2,6,6‐tetramethyl‐1‐piperidinyloxyl) as a catalyst and air as a green oxidant. They fetched numerous benzimidazole moieties ( 82 ) in 83–93% yield at 110°C under solvent‐free conditions in 24–30 h (Scheme , Table , entry 1) . While in a similar attempt by this group, target product 84 was synthesized by aerial oxidation of reactants, benzyl alcohols ( 83 ), and o ‐phenylenediamines ( 4 ) in 69–85% yield under solvent‐free conditions.…”
Section: Oxidative Coupling Of O‐phenylenediamine Using Transition Mementioning
confidence: 99%
“…Inspired by the iron-mediated catalytic system reported by Xu and co-workers for the preparation of imines through aerobic oxidative coupling of amines under air, 21 Lu and co-workers demonstrated that the aerobic oxidative cyclocondensation of benzylic primary amines (1.2 equiv) and o-phenylenediamine (1 equiv) can be achieved by the synergistic combination of Fe(NO 3 ) 3 (5 mol%) and electron-deficient 2,2,6,6-tetramethylpiperidin-1-yloxy radical (TEMPO) (5 mol%), under solvent-free conditions in air. 22 Variously substituted benzylic amines were converted into 2-substituted benzimidazoles in high yields (78-93%) at 110 °C for 24-28 hours. The first step of the proposed reaction mechanism consists of the aerobic Fe/TEMPO-catalyzed oxidation of benzylic amine to the corresponding benzylimine intermediate in a way reminiscent of that reported by Hu and Kerton for the aerobic Cu/TEMPO-catalyzed version (Scheme 9).…”
Section: Scheme 8 Possible Pathways For the Copper-catalyzed Aerobic mentioning
confidence: 99%